Augmented Reality Technology for Increasing the Understanding of Traffic Signs - Nisaul Barokati Seliro Wangi; M. Hafidh Nashrullah (STAI Miftahul Ula Nganjuk, 2019)
The problem in urban areas which has always been the topic of discussion is the discipline of city residents regarding traffic regulations that still need to be improved. Some commonly used methods to increase understanding of traffic signs have been carried out by related parties including counseling at school and as a condition for obtaining a SIM. But the method used has a less interactive and attractive appearance, and is not practical to carry anywhere. This study provides a solution to these problems by utilizing smartphones and augmented reality (AR) technology. Smartphone has now become one of the needs that can not be separated from human life, where almost everyone and even children can operate it. In addition, AR technology has also been widely used as a learning medium, one of which is as a medium for the introduction of traffic signs. Through the ability of AR in combining the real world and the virtual world at one time, the application of AR produced by this study was able to increase people's understanding of traffic signs by being more interactive, interesting and practical.